2013
DOI: 10.5194/acp-13-10517-2013
|View full text |Cite
|
Sign up to set email alerts
|

Filamentary structure in chemical tracer distributions near the subtropical jet following a wave breaking event

Abstract: Abstract. This paper presents a set of observations and analyses of trace gas cross sections in the extratropical upper troposphere/lower stratosphere (UTLS). The spatially highly resolved (≈0.5 km vertically and 12.5 km horizontally) cross sections of ozone (O 3 ), nitric acid (HNO 3 ), and peroxyacetyl nitrate (PAN), retrieved from the measurements of the CRISTA-NF infrared limb sounder flown on the Russian M55-Geophysica, revealed intricate layer structures in the region of the subtropical tropopause break.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 61 publications
2
38
0
Order By: Relevance
“…Therefore, the spatial structure of young air masses characterized by enhanced values of emission tracers from India/China resembles a bubble within the upper troposphere. These air masses are transported eastwards along the subtropical jet and most likely enter the extratropical lower stratosphere driven by Rossby wave breaking events associated with double tropopauses (e.g., Vaughan and Timmis, 1998;Castanheira and Gimeno, 2011;Ungermann et al, 2013;Homeyer and Bowman, 2013;Homeyer et al, 2014). Our simulations show that after entering the lower stratosphere, these air masses are mixed irreversibly with the surrounding stratospheric air.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Therefore, the spatial structure of young air masses characterized by enhanced values of emission tracers from India/China resembles a bubble within the upper troposphere. These air masses are transported eastwards along the subtropical jet and most likely enter the extratropical lower stratosphere driven by Rossby wave breaking events associated with double tropopauses (e.g., Vaughan and Timmis, 1998;Castanheira and Gimeno, 2011;Ungermann et al, 2013;Homeyer and Bowman, 2013;Homeyer et al, 2014). Our simulations show that after entering the lower stratosphere, these air masses are mixed irreversibly with the surrounding stratospheric air.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies also found intrusions of tropospheric air into the lower stratosphere associated with extratropical double tropopauses (e.g., Pan et al, 2009;Homeyer et al, 2011;Vogel et al, 2011b;Schwartz et al, 2015;Wu and Lü, 2015). Further, it was shown that double tropopauses are frequently associated with Rossby wave breaking events along the subtropical jet (e.g., Vaughan and Timmis, 1998;Castanheira and Gimeno, 2011;Ungermann et al, 2013;Homeyer and Bowman, 2013;Homeyer et al, 2014).…”
Section: Isentropic Transport Pathways Into the Lower Stratospherementioning
confidence: 94%
“…The better reproduction of thin vertical layers is important for the analysis of mixing processes in the upper troposphere/lower stratosphere. The algorithm is therefore currently used to process further CRISTA-NF data (Ungermann et al, 2012b) and initial (non-tomographic) measurements by GLORIA (Gimballed Limb Observer for Radiance Imaging of the Atmosphere; see Ungermann et al, 2010b). This technique might also be used to more reliably derive constant and slowly varying instrument parameters, which cannot be determined from pre-or post-flight calibration.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the characteristics of poleward advection of upper-tropospheric air have shown that such intrusions are associated with Rossby wave breaking in the upper troposphere (Peters and Waugh, 1996). In turn, poleward Rossby wave breaking has been associated with the presence of double tropopauses (DTs) (Pan et al, 2009;Castanheira and Gimeno, 2011;Homeyer et al, 2011;Ungermann et al, 2013). Further, climatological studies have found that DT occurrence in the Northern Hemisphere coincides with zones of storm track cyclogenesis (e.g., Añel et al, 2008;Peevey et al, 2012) and their occurrence frequency shows a strong seasonal variation peaking during winter (Randel et al, 2007;Manney et al, 2014), both char-acteristics displayed by the mini-hole events.…”
Section: F Millán and G L Manney: Ozone Mini-holes In Reanalysesmentioning
confidence: 99%